The Influence of Family Support and Risk Taking on Entrepreneurial Intentions of Vocational School Students - Nurul Muthmainna -; Hilwa Anwar; Andi Nasrawaty Hamid (Polteknik Ilmu Pemasyarakatan, 2023)
Vocational High School is an Indonesian educational institution that aims to produce graduates who are ready to enter the world of work and able to compete. In fact, most vocational school graduates are unemployed compared to other graduates. One effort to reduce poverty is to create businesses for young people. Entrepreneurial behavior can be determined from entrepreneurial intentions, the higher the student's entrepreneurial intentions, the greater the entrepreneurial behavior. The aim of this research is to determine the influence of family support and risk taking on vocational school students' entrepreneurial intentions. The research subjects were 223 class XI vocational school students. The data collection technique uses a scale. The sampling technique uses accidental sampling. The results of the multiple linear regression analysis have a significance value of 0.00 so that there is an influence of family support and risk taking on entrepreneurial intentions and the adjusted R square is 0.19.6, which means that family support and risk taking contribute to entrepreneurial intentions by 19.6%, while 80 The remaining .4% is influenced by other factors not studied. The conclusion is that family support and risk taking have a positive and significant effect on vocational school students' entrepreneurial intentions.